2009
DOI: 10.4321/s0365-66912009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Tumores de la conjuntiva

Abstract: Conjunctival tumors are one of the most frequent of the eye and adnexa. They comprise a large variety of conditions, from benign lesions such as nevus or papilloma, to malignant lesions such as epidermoid carcinoma or melanoma which may threaten visual function and the life of the patient. They can arise from any cellular component, but the most frequent are of epithelial and melanocytic origin. Early diagnosis is essential for preventing ocular and systemic spread and to preserve visual function. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
0
23
0
2
Order By: Relevance
“…They noted two out of nine SCC cases HIV positive whereas in our study none of the case of SCC was HIV positive. Lee SB et al (2000) and Saronil MA et al (2009) have stated infection by HIV virus to be amongst a known predisposing factor for SCC.…”
Section: Discussionmentioning
confidence: 99%
“…They noted two out of nine SCC cases HIV positive whereas in our study none of the case of SCC was HIV positive. Lee SB et al (2000) and Saronil MA et al (2009) have stated infection by HIV virus to be amongst a known predisposing factor for SCC.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up protocol after each session included measurement of visual acuity and intraocular pressure, Schirmer test and tear film breakup time, and biomicroscopy studies with seried photographs, which showed progressive regression of the tumor (Figs. 3,4,5). During the radiotherapy period and until 1 month later, the patient received topical anti-inflammatory diclofenac, eyedrops, and artificial tears.…”
Section: Case Reportmentioning
confidence: 94%
“…It is the most common type of ocular surface neoplasm, usually appearing in older patients, predominantly men. 2,3 The main risk factors associated with CCIN are infection by human papilloma virus or human immunodeficiency virus and exposure to ultraviolet rays. The most widely used treatment is complete resection, with or without adjuvant treatments such as cryotherapy, topical chemotherapy with mitomycin C, 5-fluorouracil, or interferon alpha-2b.…”
mentioning
confidence: 99%
“…A review of the 360 cases of conjunctival tumors diagnosed at the Ocular Oncology Unit of the Valladolid University Hospital revealed that 124 (39.6%) were of epithelial origin and only 11 were malignant CSCC [4]. This is the first case of recurrence and intraocular invasion treated with enucleation of the eye.…”
Section: Discussionmentioning
confidence: 99%